State forestry for America - Thoburn, Joseph B. (My University, 1893)
Introduction: Of the nature and extent of the original or native forests of the United States, of their destruction aud. The consequent effect upon the climate and upon economic conditions much has been written and much more might be written. Suffice it to say that the forests of America were entrusted to the care of private ownership and that they have disappeared not alone as the result of wasteful and improvident use but also because of wanton destruction that more land might be cultivated. Thus, always destroying, never replanting, is it strange that Americans have learned to underestimate the value of the forest, or that successive generations of such training has branded ours as a nation of forest vandals? With the growth of a market for forest products in the arts and in the commerce, this vandalism has amounted to almost universal destruction, vast areas being demanded of their timber by the lumberman’s axe without any effort being made to replace the growth. Thus gradually have the great natural forests disappeared, until today, but a small fraction of the original amount is left standing. With the limit of forest destruction almost reached, with a lumber famine not far distant and prices already advancing, the prodigality of the past forces the problem of future resources upon us.
Citation: Thoburn, Joseph B. State forestry for America. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Forests; America; Destroying; Market; Future resources; Theses; Manuscripts (documents)